Teaching and research staff at Swedish universities – A view through the lens of internationalization and diversity - Silander, Charlotte; Pietliä, Maria (Högre utbildning, 2023)
The topics of internationalization, international recruitment, and diversity have been increasingly emphasized in the agendas of Swedish universities. This study presents an overview of how Swedish universities’ teaching and research staff, with a special emphasis on national background and gender, were distributed within three job categories (career development positions, lecturerships, and professorships) and in two major fields of academic sciences in the time frame 2008–2018. We used data from Statistics Sweden to categorize groups of staff focusing on the origin of staff and the origin of their parents. We differentiated the findings by gender. The results show a large increase in the number and share of foreignborn (international) staff among career development positions and a smaller increase among lecturers and professors. The share of foreign-born staff in career development positions has markedly increased in both the hard and soft sciences. In contrast, the share of descendants of immigrants has remained quite low and stable in all the three job categories. The fact that the growth among foreign-born staff does not seem to be reflected in the composition of staff in permanent positions indicates a “contained diversity” where internationalization is strongly emphasized within non-permanent staff categories, whereas the composition in the most prestigious academic positions remains more homogeneous.